Implementation of Cooperative Learning Model STAD (Student Teams Achievement Division) Integrated Media on Students Learning Outcomes in The Matter of Salt Hydrolysis - Derin Putri Sianipar; Indriati Aulia; Ajat Sudrajat (Pascasarjana Universitas Negeri Medan, 2016)
Abstract. This study aims to investigate the differential of students’ learning outcome in salt hydrolysis between cooperative learning model type STAD (Student Teams Achievement Division) integrated Concept Map media, Powerpoint and Macromedia Flash. Population in this study was all students in grade XI IPA at SMAN 8 Medan Academic Year 2015/2016. Sample of this study consist of 3 classes that were collected in purposive sampling and using RAL (completely randomized design). The data that were collected are students’ learning outcomes. It was collected by using research instrument that is objective test with five answer choices. Based on validation test’s result, reliability, difficulty level test, power difference test, and instrument test’s distractor, then from 40 questions, 21 of it has been qualified but only 20 were used in this study. The result showed there was a difference of students’ learning outcomes in salt hydrolysis between cooperative learning model type STAD (Student Teams Achievement Division) integrated Concept Map media, Powerpoint and Macromedia Flash. The data that were collected are Fcount> Ftable (13,37> 3,10) and sign(0,00) < α (0,05). With mean values 70,16 (Experiment 3), 69,83 (Experiment 2), and 57,83 (Experiment 1) or in other words Macromedia Flash > PPT >Concept Map. Keywords: learning outcome, Cooperative Type STAD, media